'Lockdown's changed everything': Mothering adult children in prison in the UK during the COVID-19 pandemic. (December 2021) - Lockwood, Kelly
The COVID-19 pandemic occurred at a time when families of prisoners were gaining visibility in both academia and policy. Research exploring the experiences of families of prison residents has tended to focus on intimate partners and children, despite parents of those in prison being more likely than partners or children to maintain contact. The small body of work focusing on parents has identified their continued care for their children and highlights the burden of providing this care. With the ethics of care posing an ideological expectation on women to provide familial care, the care for adult children in custody is likely to fall to mothers. However, with restricted prison regimes, the pandemic has significantly impeded mothers' ability to provide this 'care'. Adopting a qualitative methodology, this paper explores the accounts of mothers to adult children in custody during the pandemic across two UK prison systems, England and Wales, and Scotland; exploring the negotiation of mothering in the context of imprisonment and the pandemic and highlighting important lessons for policy and practice.